Factibilidad técnica y económica comparativa por adherencia, entre los morteros tradicionales y el mejorado con aditivo para edificaciones - Calero Proaño, Laura de Jesús (2019)
The buildings have as a principle security, stability and economy, therefore, technically and economically optimizing the plastering of the structural parts represents contributing to the development of engineering. The research aimed to optimize the comparative feasibility between traditional and improved mortars with additives that are used for plastering in buildings. Three additives that lead marketing in the country were investigated. Currently the additives are marketed based on improving the adhesionresistance of the mortar, which has been little analyzed technical and economic compared to traditional mortar, in addition, there are no studies to determine indicators that relate the adherence with the age of the structural component. The research has an experimental and quantitative approach and raised more than 200 records. Beam type concrete witnesses were prepared, to which, depending on the age, they were plastered and the resistance by adhesion of the applied mortar was determined by the TESTER equipment. It was determined that the bond strength of the mortar is a direct function of the beam's age. Valuing the relation by resistance of adhesion and costs of the traditional mortar with B / C = 1, it was determined that the best comparative feasibility is of mortar type C with B / C of 1.21, while types A and B present costs and adhesions inferior to the traditional one. Research scientifically contributes to the development of buildings and generates spaces for new research that impact on optimizing the stability and economy of the building.